PENGARUH UKURAN PARTIKEL SERBUK EVAPORATION BOATS DALAM PEMBUATAN KOWI (CRUCIBLE) TERHADAP KEKUATAN IMPACT DAN STRUKTUR MAKRO - Jurdan Fulandy Siswoyo; Rusiyanto Rusiyanto; Rahmat Doni Widodo; Sunyoto Sunyoto; Deni Fajar Fitriyana (Jurnal Rekayasa Mesin, 2023)
Kowi or crucibles come from refractory materials. This study aims to determine the effect of the powder particle size of evaporation boats on impact resistance and macro structure. The research method used is experimental research. The variation applied was a variation of the particle size of the evaporation boats (80, 100, and 120 mesh) as much as 50% (grams) mixed with 25% (gram), kaolin, and 25% (gram) mortar. The mixture of these ingredients is added 15% (grams) of water from the total weight of the mixture. Mixing using a mixer for 1 hour and adding water. Then the material is put into a specimen mold with ASTM D256 standards and compacted at 60kg/cm2 using a hydraulic press. Sintering at 1000ËšC was carried out using an oven with a heating rate of 5ËšC / minute and a holding time of 2 hours. The highest impact price on average of 0.002828936 Joule/mm2 was obtained for the use of mesh 120 evaporation boats particle size and the lowest average impact price of 0.002633081 Joule / mm2 was obtained for the use of mesh 80 evaporation boats powder particle size. The macro structure of firing results and the best density is obtained from the use of the mesh 120 and 100 evaporation boats particle size and a fracture occurs on the flatter surface of the specimen than 80 and 100 evaporation boats mesh.